Kepemimpinan Ideal di Era Milenial - Kartika, Ika; Fajrul Hamdi Barmawi; Yuningsih, Neni; Ratu Asma; Umar Mone (IAI Nasional Laa Roiba Bogor, 2024)
Leadership is an important thing in social life. There is no doubt about it. The election of leaders has become a party in various countries around the world including Indonesia. Ideal leadership for the millennial generation must be able to adapt to the demands and development of the times. Even though the existence of leadership varies and each has its value and effectiveness, of course the thing that stands out in ideal leadership for the millennial generation is servant leadership which has the strongest relationship, for the millennial generation, the ideal of a leader is characterized by how much the leaders understand the media (technology literacy). When leaders in the millennial generation are not technologically literate, they will be ready to be abandoned by their followers.